2005
DOI: 10.1073/pnas.0409782102
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to nicotine causes deficits associated with a loss of nicotinic receptor function

Abstract: We investigated the role played by ␤2-containing neuronal nicotinic receptors [nicotinic acetylcholine receptors (nAChRs)] in mediating nicotine's side effects in the fetus and newborn. Pregnant WT and mutant mice lacking the ␤2 nAChR subunit were implanted with osmotic minipumps that delivered either water or a controlled dose of nicotine. Subsequently, we compared the development of the sympathoadrenal system and breathing and arousal reflexes of offspring shortly after birth, a period of increased vulnerabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 44 publications
3
97
2
Order By: Relevance
“…8 E (mean change in the frequency, 12 Ϯ 6%; n ϭ 8), C, G (mean increase, 98 Ϯ 36%; n ϭ 6)]. These electrophysiological findings complement recent behavioral studies on the effects of prenatal nicotine exposure and nAChR mutant mice (Cohen et al, 2005) …”
Section: Exposure To Nicotine During Mid-prenatal and Early Perinatalsupporting
confidence: 74%
See 1 more Smart Citation
“…8 E (mean change in the frequency, 12 Ϯ 6%; n ϭ 8), C, G (mean increase, 98 Ϯ 36%; n ϭ 6)]. These electrophysiological findings complement recent behavioral studies on the effects of prenatal nicotine exposure and nAChR mutant mice (Cohen et al, 2005) …”
Section: Exposure To Nicotine During Mid-prenatal and Early Perinatalsupporting
confidence: 74%
“…The mechanism underlying this upregulation of inhibitory tone remains to be explained. One simple explanation is that the loss of presynaptic nAChRs in nicotine-exposed mice may alter GABA release at LH synapses (Cohen et al, 2005).…”
Section: Prenatal Exposure To Nicotinementioning
confidence: 99%
“…Nicotinic currents have also been reported in low-threshold spiking interneurons in layers II/III and V of visual cortex in young rats (Xiang et al, 1998), and of prefrontal cortex in young mice (Couey et al, 2007). It has been shown that knock-out mice deleted for all ␤2-containing nicotinic receptors have deficits in cortically mediated arousal processes (Granon et al, 2003;King et al, 2003;Cohen et al, 2005;Granon and Changeux, 2006). Interestingly, it has been found that the performance of these mice on a behav- ioral task of arousal can be normalized if ␤ 2 subunits are restored in corticothalamic neurons during the first 3 weeks of postnatal development (King et al, 2003).…”
Section: Developmental Changes In Layer VI Nicotinic Receptorsmentioning
confidence: 99%
“…Remarkably similar deficits are detected in pups lacking β2-containing nAChRs. Loss-of-function of these nAChRs reproduces many of the abnormalities caused by perinatal nicotine exposure suggesting that nicotine's detrimental side effects on a range of crucial defensive reflexes involve loss of function of nAChR subtypes, possibly via activity-dependent desensitization [108] .…”
Section: Effects Of Perinatal Nicotine Exposure On Neonatal Respiratomentioning
confidence: 99%